Improving the International Monetary System : Constraints and Possibilities - Goldstein, Morris (Occasional Papers; Occasional Paper ;, 1995)
This study addresses major policy issues associated with the future of the international monetary system. It focuses on whether there is a need for fundamental reform of this system, defined as systematic and sustained effort on the part of the three major industrial countries (United States, Japan, and Germany) to maintain their exchange rates within agreed ranges. It then discusses less rar-reaching reforms that could strengthen and improve the system.